Pembangunan Berkelanjutan Di Era Revolusi Industri 5.0 Dari Sudut Pandang Teknik - Lifia Citra Ramadhanti; Rakay Edhiargo Toyosito (DPPM Universitas Pelita Bangsa, 2022)
Engineering is one of the construction activities that affect the natural environments as fundamental as the explorations of materials, design, construction, post-construction and other processes and result in the consumption of energy in large quantities and will continue to produce waste, and this problem will lead to changes significant in the ecological environment. Therefore, as one of the pillars in the construction industry, not only need develop engineering to meet the needs of engineering of economic and social development solely but also pay attention to environmental protection, resource conservation and promote sustainable development strategy. The reason mentioned above and to better understand the concept of sustainable development, this research seeks to study sustainable development strategy from an engineering perspective and discuses sustainable development from the pre eliminate design stage, technical design and construction implementation. Keywords: Engineering, Industry 5.0, Sustainable Development